PENGARUH CITRA MEREK, KUALITAS PELAYANAN DAN PROMOSI TERHADAP MINAT BELI KONSUMEN PADA TOKO SEMADHI BIKE SHOP BLAHKIUH DI MASA PANDEMI CORONA (COVID-19) - Robert Brosnan; Ni Putu Nita Anggraini; Ary Wira Andika (EMAS, 2021)
The purpose of this study was to test and obtain empirical evidence of the effect of brand image, service quality, and promotion on purchase intention. The population in this study were consumers in the Semadhi bike shop Blahkiuh. The sample in this study were 130 respondents who were determined based on the non-probability sampling method, namely purposive sampling. The data analysis technique used is multiple linear regression. The results of this study indicate that brand image, service quality, and promotion have a positive and significant effect on purchase intention.